Respuesta :
[tex] - 10 + 2 \frac{1}{3} \div \frac{3}{4} = [/tex]
[tex] - 10 + \frac{7}{3} \div \frac{3}{4} = [/tex]
[tex] - 10 + \frac{7}{3} \times \frac{4}{3} = [/tex]
[tex] - 10 + \frac{7 \times 4}{3 \times 3} = [/tex]
[tex] - 10 + \frac{28}{9} = [/tex]
[tex] \frac{ - 10}{ 1} + \frac{28}{9} = [/tex]
[tex] \frac{ - 90}{9} + \frac{28}{9} = [/tex]
[tex] \frac{ - 90 + 28}{9} = [/tex]
[tex] \frac{ - 90 - ( - 28)}{9} = [/tex]
[tex] \frac{ - (90 - 28)}{9} = [/tex]
[tex] \frac{ - 6 2}{9} = [/tex]
[tex] - 6 \frac{8}{9} [/tex]